(Nano)tag–antibody conjugates in rapid tests. Issue 27 (18th June 2021) - Mahmoudi, Tohid; Pourhassan-Moghaddam, Mohammad; Shirdel, Behnaz; Baradaran, Behzad; Morales-Narváez, Eden; Golmohammadi, Hamed
Abstract : Antibodies are naturally derived materials with favorable affinity, selectivity, and fast binding kinetics to the respective antigens, which enables their application as promising recognition elements in the development of various types of rapid tests. Abstract : Antibodies (Abs) are naturally derived materials with favorable affinity, selectivity, and fast binding kinetics to the respective antigens, which enables their application as promising recognition elements in the development of various types of biosensors/bioassays, especially in rapid tests. These tests are low-cost and easy-to-use biosensing devices with broad applications including medical or veterinary diagnostics, environmental monitoring and industrial usages such as safety and quality analysis in food, providing on-site quick monitoring of various analytes, making it possible to save analysis costs and time. To reach such features, the conjugation of Abs with various nanomaterials (NMs) as tags is necessary, which range from conventional gold nanoparticles to other nanoparticles recently introduced, where magnetic, plasmonic, photoluminescent, or multi-modal properties play a critical role in the overall performance of the analytical device. In this context, to preserve the Ab affinity and provide a rapid response with long-term storage capability, the use of efficient bio-conjugation techniques is critical. Thanks to their prominent role in rapid tests, many studies have been devoted to the design and development of Abs–NMs conjugates with various chemistries including passive adsorption, covalent coupling, and affinity interactions. In this review, we present the state-of-the-art techniques allowing various Ab–NM conjugates with a special focus on the efficiency of the developed probes to be employed in in vitro rapid tests. Challenges and future perspectives on the development of Ab-conjugated nanotags in rapid diagnostic tests are highlighted along with a survey of the progress in commercially available Ab–NM conjugates.